Uniform Crime Reports (United States): Supplementary Homicide Reports With Multiple Imputation, Cumulative Files 1976-2007 - Fox, James Alan ([Verlag nicht ermittelbar], 2009)
These data provide incident-level information on criminal homicides including location, circumstances, and method of offense, as well as demographic characteristics of victims and perpetrators and the relationship between the two. To adjust for unit missingness, a multiple imputation approach and a weighting scheme were adopted, resulting in a fully-imputed SHR cumulative database of criminal homicides for the years 1976-2007. Unlike other versions of the SHR files, these are limited to incidents of murder and non-negligent manslaughter, excluding justifiable homicides, negligent manslaughter and homicides related to the September 11, 2001, terrorist attacks.